Post-traumatic stress disorder symptoms in healthcare workers: a ten-year systematic review: Post-traumatic stress disorder symptoms in healthcare workers - d'Ettorre, Gabriele; Pellicani, Vincenza; Ceccarelli, Giancarlo (Acta Biomedica Atenei Parmensis, 2020)
Background and aims: Healthcare workers (HCWs) employed in hospital settings frequently experience many occupational stressors leading to post-traumatic stress disorder (PTSD) symptoms. Literature has increasingly highlighted PTSD as a major issue that involves both staff and healthcare organizations; the consequences of PTSD may include medication errors and lower standards of care. The current COVID-19 pandemic poses the need for preventing PTSD in HCWs working closely with COVID-19 patients. The purpose of this systematic review was to analyze the latest developments in assessing and managing the occupational risk of PTSD symptoms in hospital HCWs. Methods: We searched for publications in MEDLINE/Pubmed using selected keywords. Each article was reviewed and categorized into one or more of the following four categories based on its subject matter: risk assessment, risk management and occurrence rates. Results: Our search resulted in a total of 32 publications that matched our inclusion criteria.  Increased years of service, older age, previous year exposure to violence, personality traits (i.e. neuroticism), history of mental disorders, being non-graduates, were found to be workers’ pre-trauma factors predicting PTSD symptoms. Conclusions: The findings suggest the need to prioritize preventative interventions aimed to anticipate the effects of traumatic exposure by training HCWs in evidence based anticipatory methods of coping with stressful events. With regard to the current COVID-19 pandemic, we found evidence of the need to strength social support and training targeted at psychological skills of medical staff who treated COVID-19 patients.